Investigation on Effective Heat Conductivity of Fibrous Assemblies by Fractal Method (Journal of Fiber Bioengineering and Informatics, 2018)
A fractal model for predicting the effective heat conductivity of fibrous assemblies was established.In the model, fiber-to-fiber contact influence on solid heat conductivity was taken into consideration.Radiative heat conductivity was also considered to get the effective heat conductivity. The effectiveheat conductivity was proved to be related to the following parameters, including the pore area fractaldimension, tortuosity fractal dimension, maximum and minimum pore diameters, solid conductivity, airconductivity, porosity and the ratio of the number of perpendicular channels to the total number ofchannels. Experiment was conducted to verify the model, and good agreement was found between theexperimental and theoretical results.